Sejarah Metode Dakwah Rosulullah di Madinah - Spando, Iban Idha Trisda (Lembaga Yasin AlSys, 2023)
This research is motivated by the historical importance of the da'wah of the Prophet in Medina, we as people need to imitate, imitate and practice the deeds that the prophet did during his da'wah. Nabi Muhammad SAW exemplified preaching to his people in various ways through speech, writing and deeds. This type of research is library research or library research. using various data materials taken from the library in the form of books, encyclopedia dictionaries, scientific articles, literacy studies, and the internet. The preaching of the Prophet Muhammad is the most successful preaching in history, namely within a period of several years the Prophet Muhammad was able to change the order of Arab society which was said to be during the Jahiliyyah era into a civilized society based on Islamic values. Medina is the birthplace of the new religion of Islam after the da'wah space in Mecca feels cramped for Muslims. Allah SWT chose Medina as a place to form the first Islamic society, while this Medina can be used as an example.